A compendium of readings in finance and country governance - Mohd Ashhari, Zariyawati; Soh, Wei Ni (Universiti Putra Malaysia Press, 2018)
This book is a collection of separately written papers. The cover related subjects in the field of finance and governance. The objective of this book is to share findings of empirical results in the field of corporate finance; investment and country governance that have been carried out both in the international and Malaysian content. Though these papers have not been published or presented elsewhere, they should serve as first reading of current issues in finance and country governance for students who are starting to do research. The content of this book would also provide valuable input to other researchers, policymakers and relevant agencies.